THE EFFECTIVENESS OF CHOKING MANAGEMENT SIMULATION ON FIRST AID KNOWLEDGE FOR CHOKING IN PKK MOTHERS OF GIRI PENI WATES - Muhaji, Muhaji; Endah Tri Wulandari (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Choking can cause serious respiratory disorders and even death if not treated immediately. Choking Management simulation is and effective method to handle choking situations. In Giri Peni Subdistrict, 7 out of 10 mothers in Giri Peni Wates have not received information about chokingmanagement using this method. Choking incidents often occur while eating or playing, and many deaths result from lack of knowledge about first aid. This study aims to determine teh effectiveness of Choking Management simulation on the knowledge of Family Welfare Empowerment (PKK) mothers regarding first aid for choking. This study used a quasy eksperiment design with a one group pretest-posttest approach and purposive sampling, involving 30 respondents. Data was collected from November 2-9, 2025 using an expert-validated questionnaire, and analyzed with Wilcoxon test. This study showed a significant increase in knowledge scores, with an average of 16,63 at pretest and 17,40 at posttest (Z value of 0,001 < 0,05). Choking Management simulatiom is beneficial for improving mother's knowledge and skills in providing first aid to choking victims.